Influence of Service Quality, Trust, and Timely Delivery of Satisfaction Customer on J&T Express Branch Cikarang West - Melani Quintania; Yudi Julius; Nandan Limakrisna (DINASTI RESEARCH, 2023)
This study aims to determine the effect of service quality, trust, and timely delivery of J&T customer satisfaction West Cikarang Branch Express. The object examined in this study is J&T West Cikarang Branch Express. The results of this study prove that service quality has an effect positive and significant to satisfaction customer, trust influential positive and significant to satisfaction customer, And accuracy time delivery influential positive And significant to satisfaction customer. While simultaneously the quality of service, trust, and timeliness delivery in a manner together influential positive and significant to satisfaction customer.